ChemInform Abstract: Palladium‐Catalyzed Synthesis of 1, 2, 3, 4‐Tetrahydro‐5H‐2‐benzazepin‐5‐ones. Issue 7 (22nd February 2013) - Okuro, Kazumi; Alper, Howard
Abstract The synthesis involves an initial aza‐Michael addition of benzylamines to Michael acceptors (II) followed by a Pd‐catalyzed cyclocarbonylation.